2004
DOI: 10.2141/jpsa.41.120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perches on Behavior, Heart Rate, Body Temperature and Locomotor Activity of Caged Hens

Abstract: This study was carried out to investigate the behavior and physiological conditions of hens housed in cages with or without perches. The physiological parameters investigated were heart rate (HR), body temperature (BT) and locomotor activity (LA) using a radiotelemetry system. Six White Leghorn hens (3*-weeks-old) were used after transmitters implantation. Following the preconditioning period for at least +* days, the behavioral and physiological data were recorded for , consecutive days, which were the data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, perches may have advantageous effect on feed conversion ratio. This may be accounted for less active behaviour in cages with perches which Braastad (1990) and Matsui et al (2004) have reported.…”
Section: Discussionmentioning
confidence: 91%
“…However, perches may have advantageous effect on feed conversion ratio. This may be accounted for less active behaviour in cages with perches which Braastad (1990) and Matsui et al (2004) have reported.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, bird activity tends to increase with increasing group size when associated with the cage area (Carey et al, 1995;Albentosa et al, 2007), which can be explained by the synchronous feeding of hens (Hughes, 1971). In addition, Matsui et al (2004) and Elson and Croxall (2006) reported a lower feed intake for birds in furnished compared with conventional cages. Furnishing cages with perches tend to decrease bird activity (Matsui et al, 2004), increase the amount of resting behavior occurring in the cage (Tauson, 1998), and provide better insulation of the hens' bodies at night when roosting on the perch (Lill, 1968).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Matsui et al (2004) and Elson and Croxall (2006) reported a lower feed intake for birds in furnished compared with conventional cages. Furnishing cages with perches tend to decrease bird activity (Matsui et al, 2004), increase the amount of resting behavior occurring in the cage (Tauson, 1998), and provide better insulation of the hens' bodies at night when roosting on the perch (Lill, 1968).…”
Section: Discussionmentioning
confidence: 98%
“…The lower FI in EC may be due to the perches. Utilization of perches in this environment increases roosting behavior, thus decreasing motor activities and increasing resting time ( Tauson, 1998 ; Matsui et al., 2004 ). Enriched colony cages had greater feeder space than CC and FR, which may have contributed to non-aggressive and non-competitive feeding behavior ( Thogerson et al., 2009 ) and may have contributed to lower FI as well as lower feed waste.…”
Section: Discussionmentioning
confidence: 99%